A-to-I RNA Editing in the Earliest-Diverging Eumetazoan Phyla. (8th April 2017) - Porath, Hagit T.; Schaffer, Amos A.; Kaniewska, Paulina; Alon, Shahar; Eisenberg, Eli; Rosenthal, Joshua; Levanon, Erez Y.; Levy, Oren
Abstract: The highly conserved ADAR enzymes, found in all multicellular metazoans, catalyze the editing of mRNA transcripts by the deamination of adenosines to inosines. This type of editing has two general outcomes: site specific editing, which frequently leads to recoding, and clustered editing, which is usually found in transcribed genomic repeats. Here, for the first time, we looked for both editing of isolated sites and clustered, non-specific sites in a basal metazoan, the coral Acropora millepora during spawning event, in order to reveal its editing pattern. We found that the coral editome resembles the mammalian one: it contains more than 500, 000 sites, virtually all of which are clustered in non-coding regions that are enriched for predicted dsRNA structures. RNA editing levels were increased during spawning and increased further still in newly released gametes. This may suggest that editing plays a role in introducing variability in coral gametes.